Arts And Culture in Developing Attitudes of Tolerance: A Case Study of Dance Education in Elementary Schools - Al Manik, Siti Khumairo' Yuli; Suryani, Tatik; Istiqomah, Istiqomah (BASICA, 2024)
This study aims to analyze the role of dance in increasing tolerance attitudes in MI/SD students. The object of the study involved 60 students from two schools, namely MI Ma'arif Sabilul Muttaqin and MI Kanzul Huda Ponorogo. The methods used were observation, interviews and surveys before and after involvement in dance activities. The results showed that involvement in dance, such as introduction to traditional and contemporary dance, group collaboration, and multicultural performances, was effective in increasing students' tolerance attitudes. They became more open to cultural differences, increased cooperation, empathy, and the ability to resolve conflicts. The challenges that emerged included differences in students' understanding of diversity and the limited time of the curriculum. In conclusion, dance has proven to be an effective learning medium in instilling tolerance values in students.